2022
DOI: 10.1186/s40001-022-00937-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and long-term prognosis of simultaneous versus staged resection in synchronous colorectal cancer with liver metastasis: a systematic review and meta-analysis

Abstract: Purpose The optimal time point for surgical resection of synchronous colorectal liver metastases (SCLMs) is still controversial. This meta-analysis evaluated the safety and long-term prognoses of simultaneous and staged resection of SCLM to provide a reference for clinical selection. Methods A systematic literature search for studies published by October 2022 was performed using PubMed, Web of Science, Embase, Scopus and Cochrane Library. The evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The significant predictors of complications were medical comorbidities and major hepatectomy, which increased the complication rate to 40%. A recent meta-analysis [ 9 ] concluded that simultaneous resection of the primary tumor and liver metastases can be the first choice in patients with resectable synchronous CLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant predictors of complications were medical comorbidities and major hepatectomy, which increased the complication rate to 40%. A recent meta-analysis [ 9 ] concluded that simultaneous resection of the primary tumor and liver metastases can be the first choice in patients with resectable synchronous CLM.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of synchronous liver metastases, concurrent with, before, or after resection of the primary colon cancer, may improve OS. A meta-analysis showed that simultaneous resection of CLM confers equivalent long-term prognosis to that of staged resection and is overall safe with similar odds of total and organ-specific complications and perioperative mortality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For synchronous CRLM, the SR approach has been studied extensively. The proposed benefits of this approach include avoiding the morbidity and complications associated with performing a second operation, such as the inherent risks of anesthesia, need for a second hospital stay, potential for increased healthcare costs, and periprocedural pain, for example [ 64 ]. Additionally, this approach has the added benefit of addressing the liver disease immediately, thereby avoiding issues where disease progression can subsequently exclude hepatectomy.…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…In conclusion, there is merit to each surgical approach, and the decision to pursue one over the other requires an individualized approach to each patient, bearing in mind that there has been no difference in survival shown between them [ 64 , 69 , 72 ].…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…Colorectal cancer (CRC) has become a predominant cancer and ranks as the second most common cause of death due to cancer worldwide ( 1 ). Liver metastases represent the major cause of CRC-related mortality ( 2 ), and synchronous liver metastases occur in up to 25% ( 3 ) of CRC patients at diagnosis.…”
Section: Introductionmentioning
confidence: 99%